Human activities trigger change in marine landscape - Anna Maria Mannino (Flora Mediterranea, 2018)
Biodiversity is undergoing rapid and worrying changes, partially driven by anthropogenic activities. Human impacts and climate change (e.g. increasing temperature and ocean acidification), which act at different spatial scale, represent the most serious threats to biodiversity and ecosystem structure and function. In this overview, the effects of anthropogenic pressures on unique and valuable Mediterranean systems, such as Cystoseira sp. pl. forest and Posidonia oceanica meadows, are examined. These complex systems, characterized by a high associated biodiversity, are regularly exposed to natural and anthropogenic pressures. Due to the central role they have for several important ecological processes in marine ecosystems, their loss can lead dramatic consequences. Since these ecosystems are often unable to recover naturally, it is necessary to reinforce their resilience. Therefore, reintroduction by transplantation and reforestation methods have been recently proposed. Considering future increase in anthropogenic and climatic pressures, understanding how these systems respond to stressors and preserving their resilience should be an essential component of any conservation management plan.